Implementation of Work from Home (WFH) Work System and Organizational Culture and Its Impact on Employee Performance - Sujatmiko (Manunggal Halim Jaya, 2025)
This study aims to investigate the implementation of Work from Home (WFH) systems and the role of organizational culture in shaping employee performance within modern organizational environments. Triggered by the widespread transition to remote work in response to global disruptions, this research adopts a qualitative approach based on an integrative literature review, synthesizing insights from 42 peer-reviewed articles and institutional reports published between 2019 and 2025. The methodological framework involves thematic content analysis of selected scholarly works, focusing on key variables such as digital readiness, cultural typology, leadership behavior, and employee experience under WFH conditions. Findings reveal that the effectiveness of WFH systems is not determined solely by technological deployment but is significantly influenced by organizational culture and leadership practices. Specifically, trust-based, inclusive, and flexible cultures are positively associated with higher employee engagement and productivity. Furthermore, the study identifies that employee performance is shaped by a balance between autonomy, role clarity, and digital social connectivity. The research also underscores the importance of sustainability in remote work ecosystems, advocating for policies that support well-being, environmental responsibility, and long-term strategic integration. These insights provide theoretical contributions to organizational behavior and remote work literature, while offering practical guidance for leaders seeking to design resilient, human-centered digital work systems. The study recommends future interdisciplinary research to explore the evolving dynamics of hybrid work, performance measurement, and organizational adaptation in a post-pandemic world.